THE EFFECT OF DIGITAL TECHNOLOGY UTILIZATION ON HOTEL SERVICE OPERATIONS AND CUSTOMER PERCEPTION - Iza Guspian; Mursyid Hasan Basri; Arman; Daniel Cristophy Dugari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study analyzes the effect of digital technology utilization on hotel service operations and customer perception in a regional hotel in Central Bangka Regency, Indonesia. The research examines how ease of use, technology-based service quality, and feature availability influence system efficiency, and how system efficiency subsequently affects customer perception. Security and privacy are also included to evaluate their direct and moderating roles. Using survey data from 134 hotel guests, the model was tested with Partial Least Squares Structural Equation Modeling. The findings show that all three technological factors significantly enhance system efficiency, which in turn strongly improves customer perception. Security and privacy also have a significant direct effect, although their moderating influence was not supported. Overall, the study highlights the importance of efficient and user-friendly digital systems in shaping customer evaluations and provides practical insights for strengthening digital service implementation in regional hotels.